Respuesta :

Given the center coordinates [tex] (h,k) [/tex] and the radius [tex] r [/tex], the equation of the circle is

[tex] (x-h)^2 + (y-k)^2 = r^2 [/tex]

So, the equation of your circle is

[tex] (x-6)^2 + (y-1)^2 = 25 [/tex]

We can plug the values from the options to see which one satisfy the equation:

A) [tex] (1-6)^2 + (11-1)^2 = 25 +100 \neq 25[/tex]

B) [tex] (2-6)^2 + (4-1)^2 = 16 +9 = 25[/tex]

So, we already found the correct option. For the sake of completeness:

C) [tex] (4-6)^2 + (-4-1)^2 = 4 +25 \neq 25[/tex]

D) [tex] (9-6)^2 + (-2-1)^2 = 9 +9 \neq 25[/tex]

Answer:

B. [tex]R(2, 4)[/tex]

Step-by-step explanation:

The equation of a circle with center [tex](h, k)[/tex] and the radius, [tex]r[/tex], is

[tex](x-h)^2+(y-k)^2=r^2[/tex]

Here, the center of the circle is at [tex]P(6, 1)[/tex] and the radius of the circle is 5 units.

So, [tex]h=6, k=1[/tex] and [tex]r=5[/tex]

Therefore, the equation of the circle is

[tex](x-6)^2+(y-1)^2=5^2[/tex]

[tex](x-6)^2+(y-1)^2=25[/tex]

Now, the point that satisfies the equation of the circle will lie on the circle.

Let us take all the points one by one.

[tex]Q(1, 11)[/tex]

[tex](1-6)^2+(11-1)^2=25\\\\(-5)^2+(10)^2=25\\\\25+100=25\\\\125=25[/tex], which is incorrect.

So, [tex]Q(1, 11)[/tex] does not lie on the circle.

[tex]R(2, 4)[/tex]

[tex](2-6)^2+(4-1)^2=25\\\\(-4)^2+(3)^2=25\\\\16+9=25\\\\25=25[/tex], which is correct.

So, [tex]R(2, 4)[/tex] lie on the circle.

[tex]S(4, -4)[/tex]

[tex](4-6)^2+(-4-1)^2=25\\\\(-2)^2+(-5)^2=25\\\\4+25=25\\\\29=25[/tex], which is incorrect.

So, [tex]S(4, -4)[/tex] does not lie on the circle.

[tex]T(9, -2)[/tex]

[tex](9-6)^2+(-2-1)^2=25\\\\(3)^2+(-3)^2=25\\\\9+9=25\\\\18=25[/tex], which is incorrect.

So, [tex]T(9, -2)[/tex] does not lie on the circle.

Hence, the point [tex]R(2, 4)[/tex] lie on the circle.

ACCESS MORE